THE IMPACT OF MEDICATION REGIMEN COMPLEXITY ON ADHERENCE TO LONG-TERM THERAPIES - MIR, SHAKEEL AHMAD; SHAKEEL, DANISH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Adherence is a multifactorial phenomenon. Medication-related factors have long been the focus of attention. However, the results are inconsistent. Methods: In a cross-sectional questionnaire-based study of outpatients, we assessed 180 patients suffering from chronic conditions. The objective of this study is to determine the impact of medication regimen complexity on adherence to long-term drug therapies. Results: 91.66% of patients receiving more than four drugs had good or high adherence. 80.94% of patients on thrice a day (or more) drug administration had good or high adherence. 91.66% of patients receiving drug therapy for more than 5 years had good or high adherence. In all other groups, the adherence was low. The adherence was significantly (p<0.05) and positively (rs=0.792 and 0.846) correlated to the frequency of drug administration and duration of treatment. Adherence was positively correlated to the number of drugs per day (rs=0.668) but the relationships were not statistically significant (p=0.102). All the correlations were large. Conclusions: We found adherence positively correlated with medication regimen complexity. An improved understanding of the determinants of medication adherence is needed. Keywords: Medication regimen complexity, Adherence, Long-term therapy, Chronic disease